Modelling Water Absorption in Dehusked Black Gram - Swami, S B; Das, S K; Maiti, B (Journal of Agricultural Engineering, 2007)
Moisture absorption in black gram was investigated at 30, 40, 50 and 60degree C using Peleg Model. The Peleg constant K1 varied with temperature. At a given temperatures lower the K1 water absorbed was lowering. The Peleg constant K2 was almost unaffected by temperature and could be used to predict the equilibrium water absorption. The Peleg's equation with predicted constants gave fairly good fit for water absorption in black gram.